Ultrasound Medical Imaging - Vray, Didier; Brusseau, Elisabeth; Detti, Valérie; Varray, François; Basarab, Adrian; Beuf, Olivier; Basset, Olivier; Cachard, Christian; Liebgott, Hervé; Delachartre, Philippe (Medical Imaging Based on Magnetic Fields and Ultrasounds, 2014)
Ultrasound (US) imaging accompanies each of us, from several months before we are born, throughout our lives. This chapter presents both the physical basics of US imaging and the main advances expected of the echography of tomorrow. It begins with a presentation of the physical principles upon which US imaging is based. Then, it details the different modes of imaging in US systems: B‐mode, M‐mode, Doppler modes, contrast and harmonic imaging. The hardware aspects are also touched upon, with a discussion of the different types of linear or sectorial probes used in clinical practice, depending on the compromise between resolution and penetration. The chapter discusses statistical analysis of the US image using the properties of the US speckle. The final part of the chapter is devoted to the advances in US image acquisition and processing which can serve as a diagnostic aid to doctors.